Seasonal variation in Emiliania huxleyi coccolith morphology and calcification in the Aegean Sea (Eastern Mediterranean) - Triantaphyllou, M.; Dimiza, M.; Krasakopoulou, E.; Malinverno, E.; Lianou, V.; Souvermezoglou, E. (Geobios, 2010)
A seasonal morphological variability is observed in Emiliania huxleyi var. huxleyi specimens, collected from discrete water samples in the Aegean Sea. Biometric analyses reveal a consistent pattern of increase in the size of coccoliths and coccospheres, including the thickness of the inner tube elements (INT), in winter/spring time low sea surface temperature and moderate productivity samples when compared with summer time high temperature–low productivity samples. The small range of salinity change in the Aegean Sea and the absence of seasonal  pattern in nutrient content do not support any association with the observed increase in E. huxleyi coccolith size. A relatively increased [HCO3-] content is observed during spring-time interval related with the increase in the coccolith size, however it remains unclear which parameter of the carbonate system causes the observed effects.